EXPLANATION OF THE PHYSICAL BASIS OF SOUND-ASSISTED TESTING IN MEDICINE (CLINIC) ON THE BASIS OF THE "SWOT-ANALYSIS" METHOD (Scientific journal of the Fergana State University, 2024)
In this article, a pedagogical analysis of the subject of "Inspection in medicine (clinic) using sound-assisted methods" is made using the "SWOT-analysis" method. In this method, each student works actively in groups. Students will be able to express their opinion independently and defend it with reasons. The teaching process conducted on the basis of new pedagogical technologies showed a significant 15% effect.